2019
DOI: 10.1093/toxsci/kfz141
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an Environmentally Relevant Phthalate Mixture During Prostate Development Induces MicroRNA Upregulation and Transcriptome Modulation in Rats

Abstract: Environmental exposure to phthalates during intrauterine development might increase susceptibility to neoplasms in reproductive organs such as the prostate. Although studies have suggested an increase in prostatic lesions in adult animals submitted to perinatal exposure to phthalates, the molecular pathways underlying these alterations remain unclear. Genome-wide levels of mRNAs and miRNAs were monitored with RNA-seq to determine if perinatal exposure to a phthalate mixture in pregnant rats is capable of modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 88 publications
3
44
0
Order By: Relevance
“…Having in mind that phthalates and bisphenol A coexist in natural environments, their combined effects require further investigation [31]. Reproductive toxicity of phthalates and bisphenol A has been investigated in binary and multicomponent mixtures, usually targeting male reproductive tract disorders, mostly after the perinatal exposure [31,[43][44][45]. For example, it has been demonstrated that prenatal exposure to the mixture of DBP and DEHP alters fetal testosterone production and insl3 gene expression in a manner that resulted in cumulative dose-additive increases in reproductive tract malformations [44,46].…”
Section: Introductionmentioning
confidence: 99%
“…Having in mind that phthalates and bisphenol A coexist in natural environments, their combined effects require further investigation [31]. Reproductive toxicity of phthalates and bisphenol A has been investigated in binary and multicomponent mixtures, usually targeting male reproductive tract disorders, mostly after the perinatal exposure [31,[43][44][45]. For example, it has been demonstrated that prenatal exposure to the mixture of DBP and DEHP alters fetal testosterone production and insl3 gene expression in a manner that resulted in cumulative dose-additive increases in reproductive tract malformations [44,46].…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that the long-term reproductive defects associated with phthalate exposure is exerted through the action of non-coding miRNAs (Scarano et al, 2019). In that study, pregnant rats were dosed with phthalate mixture in the following proportion: 21% DEHP, 35% DEP, 15% DBP, 8% DiBP, 5% BBzP, and 15% DiNP.…”
Section: Phthalates and Micrornasmentioning
confidence: 99%
“…In that study, pregnant rats were dosed with phthalate mixture in the following proportion: 21% DEHP, 35% DEP, 15% DBP, 8% DiBP, 5% BBzP, and 15% DiNP. This proportion of phthalate mixture was based on proportion of phthalates metabolites detected in urine samples from pregnant women (Zhou C. et al, 2017;Scarano et al, 2019). To examine whether exposure to the phthalate mixture is capable of altering gene expression during prostate development of the filial generation, levels of mRNAs and miRNAs genome-wide were analyzed by RNA-seq (Scarano et al, 2019).…”
Section: Phthalates and Micrornasmentioning
confidence: 99%
See 2 more Smart Citations